2022
DOI: 10.3390/ijerph19063283
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Activity Levels and Impediments in the Era of COVID-19 Based on the Health Belief Model: A Cross-Sectional Study

Abstract: Physical activity (PA) and exercise benefit both the mother and the fetus. Many pregnant women avoid or severely limit PA, leading to complications before and after delivery. This study elucidated the precise effect of each moderator variable on prenatal physical activity (PPA) by examining demographic factors, the PPA-related health belief level (HBL), and the current PPA level. The health belief model (HBM) in conjunction with the international prenatal physical activity questionnaire was used. The HBL in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…In our study, women with higher incomes were less likely to have a low PA level during pregnancy, which is in line with the reports by Galliano et al and Yu et al [13,17]. The study in Serbian women found that inadequate PA during pregnancy was more marked in low-income families, which could re ect a lack of leisure time for exercise [10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, women with higher incomes were less likely to have a low PA level during pregnancy, which is in line with the reports by Galliano et al and Yu et al [13,17]. The study in Serbian women found that inadequate PA during pregnancy was more marked in low-income families, which could re ect a lack of leisure time for exercise [10].…”
Section: Discussionsupporting
confidence: 92%
“…Factors that affect PA in pregnant women are complex and include individual demographic, physiologic, psychologic, and lifestyle factors, as well as social support and environmental factors. Researchers have showed that pregnant women who are younger, less well educated, and unemployed and those with multiple children and a lower income are less likely to engage in an adequate amount of PA [11,12,17,18]. Obstetric variables associated with PA in pregnancy include history of miscarriage, parity, and exercise and smoking status before pregnancy [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The HBM has been used to assess many differing health outcomes among pregnant women. Among pregnant women, HBM has been shown to be an effective framework regarding factors for improving nutrition and weight control and behaviors [12,13], promoting physical activity [14,15], preventing self-medication during pregnancy [16], and promoting self-care during pregnancy [17]. These decisions a woman makes during her pregnancy, including assessing the perceived benefits and barriers to adopting new health behaviors, can have an impact on her overall pregnancy health and outcomes.…”
Section: Health Belief Modelmentioning
confidence: 99%
“…However, recent researches in Canada and Australia suggested that fewer than 50% of women receive suitable guidance from professionals about healthy N&PA during the PtP period ( 13 , 14 ). This might be due to healthcare being too expensive or inaccessible in low-income regions ( 15 ) or to the coronavirus pandemic (COVID-19) and associated isolation periods ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the apps quality (esthetics, functionality, information, and engagement) varies significantly. Many lack supporting RCTs, rigorous evaluation procedures, or published protocols and generally show an absence of quality assessment ( 17 , 28 ). However, new users still choose to download such apps, and research has shown that user feedback (subjective quality) is more influential in convincing new users to download an app than RCTs and scientific evidence ( 29 ).…”
Section: Introductionmentioning
confidence: 99%